2021
DOI: 10.1073/pnas.2021516118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of sweet taste despite the conservation of sweet receptor genes in insectivorous bats

Abstract: The evolution of taste perception is usually associated with the ecology and dietary changes of organisms. However, the association between feeding ecology and taste receptor evolution is unclear in some lineages of vertebrate animals. One example is the sweet taste receptor gene Tas1r2. Previous analysis of partial sequences has revealed that Tas1r2 has undergone equally strong purifying selection between insectivorous and frugivorous bats. To test whether the sweet taste function is also important in bats wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…Finally, various in vitro experiments were conducted in order to identify why the insectivorous bats lost their ability to perceive sweetness. The researchers concluded that the VFD of the TAS1R3 version from insectivorous bats is modified, making the protein unresponsive to sugars (Jiao et al, 2021). In contrast, another study investigating 42 species of bats found that the Tas1r2 gene is under the same level of purifying selection in both fruit and insect eating bats.…”
Section: Variants In Evolutionmentioning
confidence: 99%
“…Finally, various in vitro experiments were conducted in order to identify why the insectivorous bats lost their ability to perceive sweetness. The researchers concluded that the VFD of the TAS1R3 version from insectivorous bats is modified, making the protein unresponsive to sugars (Jiao et al, 2021). In contrast, another study investigating 42 species of bats found that the Tas1r2 gene is under the same level of purifying selection in both fruit and insect eating bats.…”
Section: Variants In Evolutionmentioning
confidence: 99%
“…The loss of taste receptor function has been linked, in part, to evolutionary shifts in feeding ecology, including dietary specialization, that reduce the selective pressures on taste receptor genes (Feng et al, 2014;Jiang et al, 2012aJiang et al, , 2012bLiu et al, 2016;Zhao et al, 2010Zhao et al, , 2012. For example, sweet taste has been independently lost in multiple lineages of terrestrial carnivores, including the strictly carnivorous felids, cetaceans, vampire bats (Antinucci & Risso, 2017;Jiang et al, 2012a;Zhao et al, 2012), and insectivorous bats (Jiao et al, 2021). This loss of sweet taste has been linked to pseudogenization of the T1R2 (sweet) receptor gene following dietary shifts toward obligate carnivory (Antinucci & Risso, 2017) as the relative lack of carbohydrates in animal tissue is thought to reduce selective pressure for maintaining a functioning sweet taste receptor (Jiang et al, 2012a).…”
Section: Ack and Loss Of Ta S Te S En S E S Among Animal S Pecie Smentioning
confidence: 99%
“…Nevertheless, Zhao and Zhang (2012) pointed to mismatches between feeding specializations and taste receptor presence/absence in mammals and birds and concluded that Jiang et al’s (2012a) hypothesis is unwarranted. The role of feeding specialization in taste receptor loss has been debated since then and is currently subject of controversy and misunderstanding ( Jiang et al 2012b ; Feng and Zhao 2013 ; Liu et al 2016 ; Feng and Liang 2018 ; Jiao et al 2021 ; Zhong et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is because protein dysfunction may also result from a regulatory mutation that abolishes gene expression or an unapparent coding-region missense mutation that causes crucial change in protein structure ( Albalat and Cañestro 2016 ). It is of note that Jiao et al (2021) postulated loss of the sweet taste receptor despite apparently intact TAS1R2 and TAS1R3 in insectivorous bats based on their indifference toward sucrose, fructose, and glucose. However, the TAS1R2+TAS1R3 heterodimer of these bats responded to an artificial sweetener, neohesperidin dihydrochalcone, and possibly may respond to carbohydrates contained in insects that were not tested by Jiao et al (2021) , e.g., trehalose, the principal sugar circulating in insect hemolymph ( Gillott 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation